Inhibiting Factors for Collaborative Water Governance: A Case Study of Mount Merapi Ecosystem in Yogyakarta, Indonesia - Harjanta, Sri Lestari; Ningrum, Dyaloka Puspita (CHANNEL: Jurnal Komunikasi, 2023)
The ecosystem around Mount Merapi, Indonesia, has many potential water sources. Still, poor management and a decrease in springs may lead to a water crisis in 2029 that could affect millions of residents in Yogyakarta, Indonesia. This study aims to identify the inhibiting factors for collaborative water governance under the threat of a water crisis. This research used qualitative descriptive research with data collected through interviews, documents, and observations. The analysis involved data reduction, presentation, and conclusion drawing/verification to explore Yogyakarta's water management aspects. The study suggests that collaborative water governance involving multiple stakeholders, including non-government actors, is crucial for effective water management. The local government dominates water management, while private and community groups have minimal involvement. There is a need for more specific regulations that comprehensively regulate water management and conservation efforts in the regions. Water management in Yogyakarta is classified under traditional governance due to the limited involvement of non-government actors and the  minimal participation space provided by the regional government. A comprehensive regulation is needed to address water conservation, and complete collaboration among stakeholders is necessary to overcome obstacles in the water management crisis.